2022
DOI: 10.21037/jtd-22-1287
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of neoadjuvant immunotherapy combined with chemotherapy followed by surgical resection in patients with stage I–IIIA small-cell lung cancer: a retrospective single-arm clinical trial

Abstract: Background: Immunotherapy, chemotherapy and surgery all have significant roles in the management of small-cell lung cancer (SCLC). Neoadjuvant immunotherapy combined with chemotherapy followed by surgery has shown encouraging efficacy for resectable SCLC with a good tolerability and considerable survival benefit. However, there are still few data on whether surgery for stage I-IIIA SCLC can be performed after immunotherapy with chemotherapy. Therefore, we investigated the safety and effectiveness of neoadjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Liu et al. conducted a retrospective study and the results showed that neoadjuvant immunotherapy combined with chemotherapy followed by surgical resection is safe and effective in patients with stage I-IIIA SCLC ( 19 ). Next, Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al. conducted a retrospective study and the results showed that neoadjuvant immunotherapy combined with chemotherapy followed by surgical resection is safe and effective in patients with stage I-IIIA SCLC ( 19 ). Next, Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case reports and retrospective studies have also reported the role of neoadjuvant immunotherapy combined with chemotherapy in LS-SCLC. Liu et al conducted a retrospective study and the results showed that neoadjuvant immunotherapy combined with chemotherapy followed by surgical resection is safe and effective in patients with stage I-IIIA SCLC (19). Next, Zhang et al reported a case of more than 23 months of event-free survival after receiving neoadjuvant tislelizumab combined with chemotherapy (8).…”
Section: Discussionmentioning
confidence: 99%